Penggunaan Aplikasi Qara’a Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Pada Siswa Kelas X MAS Al-Maksum Stabat - Salsal Bila, Ahmad Sanusi Luqman, Nurmisda Ramayani (Pusdikra Publishing, 2022)
The main problem in this study is how the use of the Qara'a method can improve the ability to read the Koran correctly according to the rules of makhraj and tajwid and produce correct reading skills in Class X MAS Al-Maksum Stabat students. This study aims to make students able to read the Koran correctly, so it is hoped that reading the Koran will become a routine activity for students, so that a generation of the Koran is formed in Class X MAS Al-Maksum Stabat students. This type of research is class action research (Class Action Research) which consists of two cycles using the Qara'a method. The results showed that the results of the pre-test or pre-test showed data including the class average score of 60.00 with the percentage of completeness in the class of 27.28%, thus there were still around 72.72% of students who had to get the same influence. intensive from the Qara'a method, in cycle II the average score of students became 70.00 with the overall percentage of completeness being 77.78%, or out of a total of 36 students there were still 8 students who were categorized as having not reached the standard of reading Al-Qur' Based on the results of this study, it can be concluded that the use of the Qara'a application to improve the ability to read the Koran in class X students of Mas Al-Maksum Stabat has increased.